Perancangan Aplikasi Deteksi Stres Berbasis Website Menggunakan Metode Naive Bayes (Studi Kasus : Ikatan Persaudaraan Pemuda Masjid Al-Ihya Komplek Marinir Depok) - Demo Susanto; Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Environmental changes that are increasingly drastic and modern, increasingly fierce competition and increasing needs are getting higher so that people's lives are more vulnerable to stress. By utilizing technology, it can be an alternative for independent stress detection for al-Ihya mosque youth. An idea emerged to implement the stress detection application. With the problems above, it is necessary to design a website-based stress detection application using the Naive Bayes method. To help teenagers, Masjid al-Ihya detect stress independently and provide information about stress. Stress is a mental disorder faced by a person due to the individual's failure to fulfill his needs or desires, resulting in pressure. Data collection was carried out in several stages, namely literature study, field study using observation, interviews, and similar literature studies. Naive Bayes is a simple proballistic classifier that calculates a set of probabilities by adding up the frequencies and combinations of values ​​from a given dataset. With this application, it can provide information, education, knowledge, understanding about stress with the results of previous diagnoses or detections. Can streamline time for al-Ihya mosque youth to detect stress early and independently as an early stage of prevention